Sodium thiosulfate protects from renal impairement following hyperthermic intraperitoneal chemotherapy (HIPEC) with Cisplatin. (1st January 2020) - Laplace, N.; Kepenekian, V.; Friggeri, A.; Vassal, O.; Ranchon, F.; Rioufol, C.; Gertych, W.; Villeneuve, L.; Glehen, O.; Bakrin, N.
Abstract: Background: Cytoreductive surgery combined with hyperthermic intraperitoneal chemotherapy (HIPEC) has been shown to provide benefits in the management of peritoneal metastasis. Cisplatin (CDDP) is one of the most frequently used drugs for peritoneal infusion. A major restriction is that CDDP causes renal toxicity and acute renal failure, sometimes leading to chronic renal failure. The aim of the present study was to assess the impact of sodium thiosulfate (ST) in preventing renal impairment (RI) following HIPEC with CDDP. Methods: This prospective study assessed the RI rates for all patients who underwent HIPEC with CDDP during two successive periods: without ST (nST Period; from November 2016 to September 2017) and with ST (ST Period; from October 2017 to March 2018). During the ST Period, patients received an ST infusion at 9 mg/m 2 prior to HIPEC and at 12 mg/m 2 at the end of the procedure. RI was defined by postoperative serum creatinine >1.6 times elevation of baseline value. The impact of ST treatment was evaluated by comparison of the RI rates between the two periods. Results: During ST Period, none of 38 patients (0%) developed RI versus 11/35 patients (31.4%) during the nST Period ( p < .005); 2 of whom required definitive hemodialysis. Baseline characteristics, background circumstances, indications and laboratory parameters before HIPEC were comparable between the two groups, as well as CDDP dose use during HIPEC. Conclusion: ST appears to be an effective drug for the prevention of the renal toxicity of CDDP used for HIPEC and should be used for all such procedures.